Higher serum DHEA concentrations before and after SSRI treatment are associated with remission of major depression. (March 2017) - Hough, Christina M.; Lindqvist, Daniel; Epel, Elissa S.; Denis, Molly St.; Reus, Victor I.; Bersani, F. Saverio; Rosser, Rebecca; Mahan, Laura; Burke, Heather M.; Wolkowitz, Owen M.; Mellon, Synthia H.
Highlights: Higher baseline serum DHEA(S) predicted SSRI-induced remission in major depression. After SSRI treatment DHEA(S) remained higher in Remitters compared to Non-remitters. Remitters had higher baseline DHEA compared to healthy controls. Abstract: Background: Dehydroepiandrosterone (DHEA) and its sulfated ester DHEA-sulfate (DHEA-S), (together DHEA[S]), are the most abundant adrenal steroids in humans and are found in blood and the brain, where they function as neurosteroids with direct receptor affinities. Preclinical studies suggest that DHEA(S) has antidepressant/neuroprotective properties, and exogenously administered DHEA has shown antidepressant efficacy in humans. Nonetheless, the role of endogenous DHEA(S) levels in major depressive disorder (MDD) and antidepressant outcomes remains unclear. Methods: Morning fasting serum DHEA(S) concentrations were determined in 36 healthy, unmedicated MDD adults with Hamilton Depression (HDRS) ratings ≥17, and 75 healthy controls. MDD participants then completed eight weeks of open-label SSRI treatment before DHEA(S) levels were re-sampled; those with post-treatment HDRS ratings ≤7 were classified as "Remitters." Pre- and post-treatment DHEA(S) levels of Remitters and Non-remitters were compared, controlling for age, sex, and BMI. Results: Pre-treatment HDRS ratings did not differ between Remitters and Non-remitters ( p = 0.179). Baseline DHEA levels of Remitters were significantly higher than both Non-remitters ( p = 0.008) and controls ( p = 0.004); baseline DHEA-S levels of Remitters were also higher than Non-remitters ( p = 0.040) but did not significantly differ from controls ( p = 0.096). Non-remitters did not significantly differ from controls. Post-treatment DHEA(S) levels remained higher in Remitters compared to Non-remitters (DHEA: p = 0.013; DHEA-S: p = 0.040). Conclusions: These data suggest that higher circulating DHEA(S) levels (while unmedicated and after eight weeks of SSRI treatment) predict SSRI-associated remission in MDD. This raises the possibility that endogenous DHEA(S) abundance is a physiological adjunct to SSRI efficacy, as suggested by prior preclinical and clinical studies.